LOCAL ECONOMIC EMPOWERMENT THROUGH THE DEVELOPMENT OF MSMEs AND TOURISM BASED ON LOCAL WISDOM IN LINTANG VILLAGE, EAST BELITUNG - Ary, Maxsi; Anshori, Iedam Fardian; Hariyanti, Ifani; Rahadi, Panji Firman; Irawan, Rivaldy; Sulaeman, Aqil Tama (Indonesian Community Service and Empowerment Journal (IComSE), 2025)
Lintang Village, located in East Belitung, possessed significant potential for local economic development through micro, small, and medium enterprises (MSMEs) and tourism based on local wisdom. The village was known for its traditions and rich natural resources, such as cultivating pepper (white pepper), spices, and traditional fishing techniques. Additionally, natural attractions like Tebat Rasau and cultural sites such as Kubok Tuk Layang offered unique tourism opportunities. This study aimed to explore the economic potential of the village through approaches grounded in local wisdom and community traditions. This study aimed to explore the economic potential of the village through approaches grounded in local wisdom and community traditions. The study adopted a qualitative case study approach, with data collected through field observations, interviews with stakeholders, and document analysis. A SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis was applied to evaluate the development potential of MSMEs and tourism, identify key challenges, and formulate strategies for local economic empowerment. The findings revealed that MSMEs rooted in local wisdom had significant opportunities for growth, including honey-based products, handcrafted items made from rattan and bamboo, and organic agricultural products. Additionally, cultural and educational tourism had the potential to attract both domestic and international visitors. However, the village faced several challenges, such as a lack of support from local authorities, limited market access, and inadequate entrepreneurial training for the local community. To address these challenges, proposed strategies included digitizing village administration, providing entrepreneurial training, promoting tourism through online platforms, and collaborating with higher education institutions through community service programs and innovative research. By implementing these strategies, Lintang Village demonstrated potential to become a sustainable model for local economic empowerment based on local wisdom.